Teachers’ Perspectives on Pedagogical Approaches for Inculcating Values through Textbooks Across School Boards in West Bengal, India - Nandi, Ankur; Halder, Tarini (Indonesian Journal of Education and Social Sciences, 2026)
The integration of values in education is a key aspect of shaping learners’ character and social responsibility. Textbooks, as primary instructional tools, often embed values, but their effective inculcation largely depends on the pedagogical approaches adopted by teachers across school boards in West Bengal. The study aims to compare the opinions of CBSE and WBBSE teachers across language, social science, and science subjects regarding pedagogical approaches for inculcating values reflected in textbooks. The study employed a descriptive method with a qualitative approach. A purposive sample of 150 teachers from language, social science, and science subjects across CBSE and WBBSE schools in Bankura and Nadia districts of West Bengal was chosen. Data were gathered using three self-developed checklists that followed by the National Curriculum Framework (2023) for School Education and analysed through percentage calculations, with findings displayed in tables and graphs. CBSE and WBBSE boards strongly favor active, participatory, and literature-based pedagogical approaches for inculcating values through textbooks. Language teachers prioritize storytelling, dramatization, and cooperative learning; social science teachers emphasize discussions, role plays, and community-based activities; and science teachers prefer hands-on experiences, demonstrations, and discovery learning. The study found that language, social science, and science teachers from both CBSE and WBBSE commonly agreed on using discipline-specific pedagogical approaches for inculcating values.